2015
DOI: 10.1002/jbm.a.35495
|View full text |Cite
|
Sign up to set email alerts
|

Chondroprotective effect of zinc oxide nanoparticles in conjunction with hypoxia on bovine cartilage‐matrix synthesis

Abstract: Articular cartilage is a tissue specifically adapted to a specific niche with a low oxygen tension (hypoxia), and the presence of such conditions is a key factor in regulating growth and survival of chondrocytes. Zinc deficiency has been linked to cartilage-related disease, and presence of Zinc is known to provide antibacterial benefits, which makes its inclusion attractive in an in vitro system to reduce infection. Inclusion of 1% zinc oxide nanoparticles (ZnONP) in poly octanediol citrate (POC) polymer cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 56 publications
1
10
0
Order By: Relevance
“…Moreover, the scaffold with 10 wt% ZnO-NPs promoted osteogenic properties rather than chondrogenic differentiation, which is consistent with the findings of a previous study. 145 Mirza et al 145 studied the chondrogenic effects of 1% ZnO-NPs decorated with poly (octanediol citrate) polymer, and found that they improved chondrocyte viability, upregulated the expression of cartilage matrix-specific genes (COL2A1 and ACAN), and inhibited the expression of the matrix degradation gene (MMP-13).This cartilagepromoting ability could be attributed to Zn 2+ release. Some studies claim that Zn 2+ can enhance chondrocyte proliferation, while also preventing cartilage loss by activating the P13/Akt pathway.…”
Section: Dovepressmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the scaffold with 10 wt% ZnO-NPs promoted osteogenic properties rather than chondrogenic differentiation, which is consistent with the findings of a previous study. 145 Mirza et al 145 studied the chondrogenic effects of 1% ZnO-NPs decorated with poly (octanediol citrate) polymer, and found that they improved chondrocyte viability, upregulated the expression of cartilage matrix-specific genes (COL2A1 and ACAN), and inhibited the expression of the matrix degradation gene (MMP-13).This cartilagepromoting ability could be attributed to Zn 2+ release. Some studies claim that Zn 2+ can enhance chondrocyte proliferation, while also preventing cartilage loss by activating the P13/Akt pathway.…”
Section: Dovepressmentioning
confidence: 99%
“…Moreover, the scaffold with 10 wt% ZnO-NPs promoted osteogenic properties rather than chondrogenic differentiation, which is consistent with the findings of a previous study. 145 …”
Section: Osteogenic and Chondrogenic Abilities Of Zno-npsmentioning
confidence: 99%
“…Piezoelectric zinc oxide has not shown any toxic effects in micrometer and larger size ranges [ 101 ], but it has been demonstrated toxicity in nano size due to the production of reactive oxygen species [ 102 ]. Significant results has reported on zinc oxide nanoparticles dispersed in the polymeric scaffold along with hypoxia have shown ability to synthesis cartilage [ 103 ] . According to Material Safe Data Sheet (MSDS) databases LD50 of acute oral ZnO is 7950 mg/kg for mice shows no significant toxicity [ 104 ].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from their elastic mechanical properties for engineering of soft tissues, CA-based polyester materials could be formed into hard composites for orthopedic implants [27]. The solid material phase can be introduced in various filler forms such as ''bioglasses'' or nanoparticles [28,29]. This opportunity was explored previously for production of multi-functional scaffolds that promote chondrocyte proliferation while at the same time deplete the bacteria in their environment by controlled release of zinc oxide (ZnO) nanoparticles from biodegradable polymer matrix [28].…”
Section: Discussionmentioning
confidence: 99%
“…The solid material phase can be introduced in various filler forms such as ''bioglasses'' or nanoparticles [28,29]. This opportunity was explored previously for production of multi-functional scaffolds that promote chondrocyte proliferation while at the same time deplete the bacteria in their environment by controlled release of zinc oxide (ZnO) nanoparticles from biodegradable polymer matrix [28]. The problem of bacterial biofilm formation upon surgical intervention must be considered when designing a potential material for scaffold fabrication.…”
Section: Discussionmentioning
confidence: 99%